2001
DOI: 10.1088/0268-1242/16/4/304
|View full text |Cite
|
Sign up to set email alerts
|

The coalescence of ELO layers of InxGa1-xAs grown on patterned (111) GaAs by liquid phase epitaxy

Abstract: In x Ga 1−x As (x = 0.06) epitaxial lateral overgrown (ELO) layers were grown on (111)B GaAs patterned substrates covered with SiN x masks by liquid phase epitaxy. The thickness of the ELO layer with a {111}A growth front was found to decrease as the growth progressed. On the other hand, for the ELO layer with a {111}B growth front, this kind of decrease of thickness was found to be very small. When the layers with different growth fronts ({111}A and {111}B) coalesced, dislocations were found to be generated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…4(a). The existence of these lines are due to the coalescence of adjacent faces during growth and this kind of coalescence is a common phenomenon observed in the layers grown by epitaxial lateral overgrowth or related techniques [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…4(a). The existence of these lines are due to the coalescence of adjacent faces during growth and this kind of coalescence is a common phenomenon observed in the layers grown by epitaxial lateral overgrowth or related techniques [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16] Recently, we have shown that high-quality In x Ga 1Àx As (x ¼ 0:06; 0:10; 0: 15) can be grown in the form of a bridge over patterned GaAs substrates by liquid-phase epitaxy. [17][18][19][20][21][22][23][24] However, it is very difficult to grow In x Ga 1Àx As with higher In compositional ratio on GaAs substrates, because the lattice mismatch is very high. We have proposed a new method to grow In x Ga 1Àx As on an InAs trench substrate.…”
Section: Introductionmentioning
confidence: 99%